Prevalence of depression in the amputated patients concerning demographic variables - M.J. Khademi; M. Gharib; V. Rashedi (Afarand Scholarly Publishing Institute, 2012)
Introduction : From rehabilitation point of view, amputation is a deficit resulting in the individual's disability and subsequent psychosocial problems. This study has been conducted in order to determine Prevalence of depression in the amputated patients concerning demographic variables.   Methods & Materials : In this cross-sectional descriptive-analytic study, 160 referred to rehabilitation center of Red Crescent society of Islamic republic of Iran were included using random sampling. To gather the date, Beck Depression Inventory-II was used as well as demographic variables questionnaire. Data analysis was completed through SPSS.   Results : The sample consisted of 82 . 5% male, and 63 . 8% were married. The mean age of the sample was 37.5(SD: 5.43) and the mean years of amputation was 13.16(SD: 7.22). 74 subjects (46.25%) did not have the sign of depression, however 86 (53.75%) had somehow experienced degrees of depression. Also factors such as marital status, education level, and employment and amputation level are of significant relationship with depression.   Conclusion : The results indicated that 53.75 % of subjects were involved with depression of different severity. According to considerable amount of signs in the above-mentioned society and the significance of social support in new approaches, some useful educational programs and skill enhancement workshops is recommended so as to decrease the depression of the subjects.